Facile Construction of Silver Decorated on Carbon Nanotube in Natural Rubber and Polyethylene Blend for Antibacterial Activity - Thai, Nguyen Thi; Thu, Nguyen Thi Minh; Hoang, Do Huy; Dang, Do Van (VNU Journal of Science: Natural Sciences and Technology, 2023)
The study described the preparation of composite material through the dispersion of carbon nanotubes (CNTs) decorated with silver nanoparticles (Ag NPs) in the matrix of blending natural rubber (NR) and polyethylene (PE), for use as an antibacterial agent. The FESEM results indicated the uniform and defect-free surface of the synthesized composites. The mechanical properties of synthesized composite improved with a 65% increase in tensile strength, a 38% increase in elongation, and a 40% increase in hardness compared to the original NR/PE blend materials. Although the addition of CNTs-Ag NPs did not considerably affect the thermal stability of the NR/PE blend, it was found to prevent E. coli bacterial growth by 35%. This opens up new possibilities for the use of the composite in a variety of applications, particularly in the field of public health and wellness.